Repressor of Estrogen Receptor Activity (REA) Is Essential for Mammary Gland Morphogenesis and Functional Activities: Studies in Conditional Knockout Mice - Park, Sunghee (Endocrine Society, 2011)
Estrogen receptor (ER) is a key regulator of mammary gland development and is also implicated in breast tumorigenesis. Because ER-mediated activities depend critically on coregulator partner proteins, we have investigated the consequences of reduction or loss of function of the coregulator repressor of ER activity (REA) by conditionally deleting one allele or both alleles of the REA gene at different stages of mammary gland development. Notably, we find that heterozygosity and nullizygosity for REA result in very different mammary phenotypes and that REA has essential roles in the distinct morphogenesis and functions of the mammary gland at different stages of development, pregnancy, and lactation. During puberty, mice homozygous null for REA in the mammary gland (REA(f/f) PR(cre/+)) showed severely impaired mammary ductal elongation and morphogenesis, whereas mice heterozygous for REA (REA(f/+) PR(cre/+)) displayed accelerated mammary ductal elongation, increased numbers of terminal end buds, and up-regulation of amphiregulin, the major paracrine mediator of estrogen-induced ductal morphogenesis. During pregnancy and lactation, mice with homozygous REA gene deletion in mammary epithelium (REA(f/f) whey acidic protein-Cre) showed a loss of lobuloalveolar structures and increased apoptosis of mammary alveolar epithelium, leading to impaired milk production and significant reduction in growth of their offspring, whereas body weights of the offspring nursed by females heterozygous for REA were slightly greater than those of control mice. Our findings reveal that REA is essential for mammary gland development and has a gene dosage-dependent role in the regulation of stage-specific physiological functions of the mammary gland.